Teknis Komunikasi Dalam Peluang Usaha Photography Di Prince Studio Photography Padang - Shadikyanto, Fadjri; ., Defhany (CV. ITTC INDONESIA, 2024)
This final assignment of scientific paper writing is conducted to understand the communication efforts that can be observed in a professional interaction. In this case, the author focuses observations with the title